2011
DOI: 10.1371/journal.pbio.1001195
|View full text |Cite
|
Sign up to set email alerts
|

The Open Knowledge Foundation: Open Data Means Better Science

Abstract: Open data leads to better science, but overcoming the barriers to widespread publication and availability of open scientific data requires a community effort. The Open Knowledge Foundation Open Data in Science Working Group describes their role in this movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
222
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(253 citation statements)
references
References 6 publications
3
222
0
12
Order By: Relevance
“…The case for open access has been extensively reported in the literature [14,16,[31][32][33] 10 . Essentially, advocates of open access want full access to, and use of, published scientific articles, moved by the core argument that publicly funded universities and granting bodies have a moral duty to make academic research output available on the web at no charge.…”
Section: Open Access: the Right To Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…The case for open access has been extensively reported in the literature [14,16,[31][32][33] 10 . Essentially, advocates of open access want full access to, and use of, published scientific articles, moved by the core argument that publicly funded universities and granting bodies have a moral duty to make academic research output available on the web at no charge.…”
Section: Open Access: the Right To Knowledgementioning
confidence: 99%
“…Because the many benefits of open science have already been extensively studied and reported [10][11][12][13][14][15][16], this article instead intends to be a user guide for open science. The next sections of this article therefore provide an overview of the key pillars of open science, along with resources and tips to make open science happen in everyday research practices.…”
mentioning
confidence: 99%
“…Research needs to be open and shared to promote efficiency and trustworthiness. Sharing research materials and data enables others to (a) understand the original research protocol more completely, (b) check and verify reported analyses, (c) critique and improve the materials and protocols, and (d) reuse the materials or data for replication or other research purposes (Miguel et al, 2014;Molloy, 2011).…”
Section: Trustworthy Research Is Open Transparent and Reproduciblementioning
confidence: 99%
“…The Open Science movement strengthened the perception of the importance of data, as it is the evidence of scientific knowledge and the basis for its development [36]. Scientific data allow us to solve problems in ecology and climate, health, national security or nanotechnology [39], which confirms it to be a defining intellectual asset that can be not only peer-reviewed, but also subject to quality assessment and reuse [26].…”
Section: Introductionmentioning
confidence: 99%